Comb-like fluorine-modified polysiloxane-based solid electrolyte, preparation method and lithium battery
Patent Information
- Application Number
- CN202610746293.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-28
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-05-28
AI Technical Summary
从而解决现有聚硅氧烷基固态电解质离子电导率低以及形态稳定性-主链柔顺性不可兼得的问题
1、本发明提供了一种梳状氟改性的聚硅氧烷基固态电解质,所述梳状氟改性的聚硅氧烷基固态电解质是由聚醚胺D400和梳状氟改性的聚硅氧烷交联形成的。梳状氟改性的聚硅氧烷中,主链采用硅氧烷聚合物,具有优异的柔顺性、低玻璃化转变温度Tg、不易燃特性、出色的化学稳定性。侧链通过聚醚键进行改性,实现锂离子的迁移,并通过接枝对三氟甲基苯乙烯,在侧链引入-CF3基团,因C与F电负性差异大,电子云向F偏移并使其带负电,产生诱导效应,进一步促进Li+传输;同时,-CF3比TFSI-优先分解生成LiF,可显著提升F-QSCE的界面稳定性。最后,侧链端基的易开环的环氧乙烷基团与交联剂进行交联,增加电解质的机械性能。从而解决现有聚硅氧烷基固态电解质离子电导率低以及形态稳定性-主链柔顺性不可兼得的问题。
Smart Images

Figure CN122291679B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid electrolyte technology, specifically to comb-shaped fluorine-modified polysiloxane solid electrolyte, its preparation method, and lithium batteries. Background Technology
[0002] Lithium metal is widely used due to its high energy density, long cycle life, rapid charge / discharge capability, and environmental friendliness. However, traditional liquid lithium-ion batteries contain a large amount of organic electrolyte, leading to drawbacks such as leakage, flammability, and explosion, posing significant safety hazards. In contrast, polymer solid electrolytes offer advantages such as good safety performance, a wide operating temperature range, and long cycle life, making them a research hotspot in the lithium metal field in recent years. Furthermore, these electrolytes possess excellent mechanical properties, effectively suppressing dendrite growth in the lithium metal negative electrode during charge / discharge, thus showing great promise for applications in lithium metal batteries.
[0003] Among polymer solid electrolytes, polysiloxane-based solid electrolytes with -Si-O-Si- groups have attracted widespread attention in recent years due to their advantages such as low glass transition temperature, strong room-temperature ionic conductivity, non-flammability, excellent oxidation resistance, and good interfacial stability with lithium metal anodes. However, the application of polysiloxane-based solid electrolytes is limited by their inherent drawbacks: on the one hand, the weak coordination and dissolution ability of lithium salts in the ion-insulating Si-O-Si framework leads to low ionic conductivity. On the other hand, polysiloxanes have low glass transition temperatures and are mostly viscous liquids at room temperature, unable to exist as morphologically stable films. Therefore, it is necessary to introduce side chains with strong intermolecular interactions to promote the formation of self-standing polymer films. However, the introduction of side chains will inhibit the mobility of polysiloxane segments to varying degrees, thus affecting the flexibility of the main chain. Summary of the Invention
[0004] To address the aforementioned problems, this invention provides a comb-shaped fluorine-modified polysiloxane solid electrolyte, its preparation method, and a lithium battery. In the comb-shaped fluorine-modified polysiloxane solid electrolyte of this invention, the main chain of the comb-shaped fluorine-modified polysiloxane provides flexibility, and the incorporation of -CF3 groups on the side links generates an inductive effect, enhancing the lithium-ion battery's performance. + With F, TFSI - The interaction with C reduces Li + -TFSI - -Li + Ion pair aggregation promotes Li + The method enhances conductivity by reacting ethylene oxide at the side chain ends with polyetheramine to achieve cross-linking, thereby increasing mechanical properties. This solves the problem of low ionic conductivity and the trade-off between morphological stability and main chain flexibility in existing polysiloxane solid electrolytes.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: The first objective of this invention is to provide a comb-shaped fluorine-modified polysiloxane solid electrolyte, which is formed by blending a lithium salt with a crosslinked comb-shaped fluorine-modified polysiloxane, wherein the crosslinked comb-shaped fluorine-modified polysiloxane has the following structure: .
[0006] Where m is 21~44 and n is 6~33.
[0007] In a preferred embodiment of the present invention, the crosslinked comb-shaped fluorinated polysiloxane is formed by crosslinking polyetheramine D400 and comb-shaped fluorinated polysiloxane; the molar ratio of lithium salt to oxygen atoms in comb-shaped fluorinated polysiloxane is 1:20, and the lithium salt is lithium bis(trifluoromethanesulfonyl)imide.
[0008] In the crosslinked comb-like fluorinated polysiloxane, the main chain of polysiloxane provides flexibility, and the insertion of -CF3 groups into the side chains produces an inductive effect, enhancing the Li + With F, TFSI - The interaction with C reduces Li + -TFSI - -Li + Ion pair aggregation promotes Li + The mechanical properties are enhanced by the reaction of ethylene oxide at the side chain end with polyetheramine, which improves electrical conductivity and cross-links the material.
[0009] It should be noted that, as Figure 1 As shown, the cross-linked comb-shaped fluorinated modified polysiloxane has a main chain of siloxane polymer and a side chain of p-trifluoromethylstyrene, thus forming a comb-like structure. The specific preparation process is as follows: First, utilizing the silane-hydrogen active sites in hydrogen-containing silicone oil, under the action of a Karstedt platinum catalyst, a polyether with ethylene oxide end groups and p-trifluoromethylstyrene are grafted onto the polysiloxane side chains via a hydrosilylation reaction. Subsequently, utilizing the reactivity of the end-group ethylene oxide with amino groups, polyetheramine D400 is added to achieve cross-linking of the modified polysiloxane. The polysiloxane modified using this method can be used as a solid electrolyte. Its performance improvement strategies include the following two points: First, the network structure contains a large number of polyether segments, where oxygen atoms can coordinate with lithium ions, promoting ion transport and thus improving lithium-ion conductivity. Second, the side chains containing -CF3 groups can further promote lithium salt dissociation and enhance the interfacial stability of the electrolyte. Due to the significant difference in electronegativity between carbon and fluorine, the electron cloud shifts towards the fluorine atoms, making them negatively charged, producing an inductive effect. This effect not only enhances Li +The interaction with F, TFSI⁻ and C reduces Li + -TFSI - -Li + The aggregation of ion pairs promotes the Li + The transmission; at the same time, the -CF3 group is more efficient than TFSI. - Preferential decomposition to generate LiF can significantly improve the interfacial stability of fluorine-modified quasi-solid-state composite electrolyte (F-QSCE).
[0010] The comb-shaped polysiloxane solid electrolyte is obtained by hydrosilylation of an ethylene oxide-containing olefin with a hydrogen-containing silicone oil and trifluoromethylstyrene, followed by crosslinking and curing with a crosslinking agent, polyetheramine D400, and ethylene oxide groups, and then blending with a lithium salt. The main chain uses a siloxane polymer due to its excellent flexibility and low glass transition temperature T0. g It exhibits non-flammability and excellent chemical stability. The side chain is modified via polyether bonds to facilitate lithium ion migration. Furthermore, by grafting p-trifluoromethylstyrene, -CF3 groups are introduced into the side chain. Due to the significant electronegativity difference between C and F, the electron cloud shifts towards F, making it negatively charged, thus generating an inductive effect that further promotes lithium ion migration. + Transmission; simultaneously, -CF3 is better than TFSI - The preferential decomposition to form LiF significantly improves the interfacial stability of F-QSCE. Finally, due to the presence of ethylene oxide groups at the side chain ends, their easy ring-opening properties facilitate cross-linking with a cross-linking agent, increasing the mechanical properties of the electrolyte. This invention, through the regulation of the polysiloxane molecular structure, effectively synergizes the ionic conductivity, electrochemical stability window, flexibility, and mechanical properties of the solid electrolyte, as well as the ability to accommodate high-voltage electrodes, resulting in a flexible solid polyelectrolyte with high ion mobility and mechanical strength.
[0011] A second objective of this invention is to provide a method for preparing the above-mentioned comb-shaped fluorine-modified polysiloxane solid electrolyte, comprising the following steps: S1. Using a precursor, hydrogen-containing silicone oil, and p-trifluoromethylstyrene as raw materials, a hydrosilylation reaction is carried out in a solvent and platinum-based catalyst system to obtain a comb-like fluorinated modified polysiloxane; the structure of the precursor is shown below: ; The degree of polymerization m ranges from 21 to 44.
[0012] In a preferred embodiment of the present invention, the preparation method of the precursor includes the following steps: using polyethylene glycol monoallyl ether and chloropropylene oxide as raw materials, a substitution reaction is carried out in an ice-water bath under the action of an alkaline catalyst to obtain the precursor, wherein the precursor is allyloxy polyoxyethylene ether glycidyl ether.
[0013] In a preferred embodiment of the present invention, the molar ratio of polyethylene glycol monoallyl ether to chloropropylene oxide is 1:6 to 13; the molecular weight of polyethylene glycol monoallyl ether is 500 to 2000; the molar ratio of alkaline catalyst to polyethylene glycol monoallyl ether is 6:1, and the alkaline catalyst is sodium hydroxide.
[0014] In a preferred embodiment of the present invention, the specific preparation process of the precursor is as follows: polyethylene glycol monoallyl ether is stirred with chloropropylene oxide, sodium hydroxide is added under ice-water bath conditions, the reaction temperature is raised to 50°C to carry out the ring-opening reaction, and after completion, the reaction system is extracted and concentrated to obtain a crude product. Subsequently, the crude product is placed in a mixed solution of cyclohexane and ethanol and stirred, the solid is collected, and dried to obtain the precursor.
[0015] In a preferred embodiment of the present invention, the molecular weight of polyethylene glycol monoallyl ether is 500-2000, more preferably 2000, i.e., APEG2000. The molar ratio of APEG2000 to chloropropylene oxide is 1:6-13, more preferably 1:13; the molar ratio of sodium hydroxide to APEG2000 is 6:1; and the ring-opening reaction time is 48 h.
[0016] In a preferred embodiment of the present invention, the volume ratio of cyclohexane to ethanol in the cyclohexane-ethanol mixed solution is 10:1; the stirring time is 1 hour.
[0017] In a preferred embodiment of the present invention, the mass ratio of the precursor, the hydrogen-containing silicone oil, and p-trifluoromethylstyrene is 1230:133:103.3; the mass-volume ratio of the precursor to the solvent is 1.23 g:6 mL, and the solvent is toluene.
[0018] In a preferred embodiment of the present invention, the hydrogen content in the hydrogen-containing silicone oil is 0.75% by mass; the platinum-based catalyst is a Karstedt platinum catalyst; the hydrosilylation reaction temperature is 65℃~75℃, and the reaction time is 8h~12h. Preferably, the hydrosilylation reaction temperature is 70℃, and the reaction time is preferably 10h.
[0019] S2. Using comb-shaped fluorine-modified polysiloxane and lithium salt as raw materials, the comb-shaped fluorine-modified polysiloxane and the crosslinking agent undergo a crosslinking reaction under the action of a crosslinking agent to obtain a comb-shaped fluorine-modified polysiloxane solid electrolyte.
[0020] In a preferred embodiment of the present invention, the molar ratio of crosslinking agent to hydrogen-containing silicone oil is 1:3, the crosslinking agent is polyetheramine with a molecular weight of 400, the crosslinking reaction temperature is 80℃~90℃, and the time is 10h~14h.
[0021] The specific process of S2 is as follows: Lithium salt is added to the S1 system and stirred until dissolved. Then, the crosslinking agent polyetheramine D400 is added and the system is introduced into a polytetrafluoroethylene mold. The mold is placed in an oven and cured to obtain a comb-shaped polysiloxane, which is a comb-shaped fluorine-modified polysiloxane solid electrolyte.
[0022] In a preferred embodiment of the present invention, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide, i.e., LiTFSI.
[0023] In a preferred embodiment of the present invention, the molar ratio of oxygen atoms in LiTFSI to comb-shaped fluorinated polysiloxane is 1:20; the dissolution time is 1h to 2h; the molar ratio of polyetheramine D400 to hydrogen-containing silicone oil is 1:3; the curing temperature is preferably 85℃, and the curing time is preferably 12h.
[0024] The reaction mechanism of this invention is as follows: First, chloropropylene oxide reacts with APEG2000 in the presence of NaOH to undergo a nucleophilic substitution reaction, yielding APEG2000 with terminal epoxy groups. The reaction equation for the nucleophilic substitution reaction is as follows: .
[0025] Then, the terminal olefin of APEG2000 undergoes an addition reaction with the Si-H bonds in the hydrogen-containing silicone oil (PMHS) to obtain epoxy-terminated APEG2000 modified PMHS. The reaction equation for the hydrosilylation reaction is as follows: .
[0026] Finally, crosslinking was achieved through ring-opening reaction with terminal epoxy groups due to ring strain and nucleophilic substitution reaction with the nucleophilic reagent polyetheramine D400, yielding a product with a network structure. The reaction equation for the nucleophilic substitution reaction of D400 is as follows: .
[0027] A third objective of this invention is to provide a lithium battery comprising a positive electrode, a negative electrode, and an electrolyte; the electrolyte being the aforementioned comb-shaped fluorine-modified polysiloxane solid electrolyte.
[0028] The comb-shaped fluorine-modified polysiloxane solid electrolyte is obtained by ring-opening polyetheramine with branched ethylene oxide. As a solid electrolyte used in lithium-ion batteries, its lithium-ion conducting portion consists of polyether bonds in the polyetheramine, polyether bonds in the branched APEG, and grafted trifluoromethyl groups. In the electrolyte, polysiloxane serves as the main chain to increase membrane flexibility, while polyether and p-trifluoromethylstyrene are used as grafts to improve the ion-conducting capacity and electrochemical stability window of the solid electrolyte. Finally, the epoxy groups crosslink with the polyetheramine and p-trifluoromethylstyrene to form a comb-like structure, increasing the mechanical strength of the solid electrolyte.
[0029] In this invention, a comb-shaped fluorine-modified polysiloxane solid electrolyte is applied to a lithium metal battery. The lithium metal battery comprises a Li||SPE||LiFePO4 battery consisting of a positive electrode made of LiFePO4 and activated carbon coated on aluminum foil, the comb-shaped fluorine-modified polysiloxane solid electrolyte of this invention as the electrolyte, and lithium metal as the negative electrode. The comb-shaped polysiloxane polymer, due to the flexibility and chemical stability of its siloxane backbone, the ion-conducting properties of the modified side chain polyether and the -CF3 group, and the easy crosslinking properties of the terminal ethylene oxide, endows it with excellent interfacial stability, good ionic conductivity, and good mechanical properties when used as a solid electrolyte.
[0030] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention provides a comb-shaped fluorine-modified polysiloxane solid electrolyte, wherein the comb-shaped fluorine-modified polysiloxane solid electrolyte is formed by crosslinking polyetheramine D400 and comb-shaped fluorine-modified polysiloxane. In the comb-shaped fluorine-modified polysiloxane, the main chain adopts a siloxane polymer, exhibiting excellent flexibility and a low glass transition temperature T0. g It exhibits non-flammability and excellent chemical stability. The side chain is modified via polyether bonds to facilitate lithium ion migration. Furthermore, by grafting p-trifluoromethylstyrene, -CF3 groups are introduced into the side chain. Due to the significant electronegativity difference between C and F, the electron cloud shifts towards F, making it negatively charged, thus generating an inductive effect that further promotes lithium ion migration. + Transmission; simultaneously, -CF3 is better than TFSI - The preferential decomposition to form LiF significantly improves the interfacial stability of F-QSCE. Finally, the easily ring-opening ethylene oxide groups at the side chain end groups crosslink with the crosslinking agent, increasing the mechanical properties of the electrolyte. This solves the problems of low ionic conductivity and the incompatibility between morphological stability and main chain flexibility in existing polysiloxane solid electrolytes.
[0031] 2. This invention provides a method for preparing comb-shaped fluorine-modified polysiloxane solid electrolyte. Using polyethylene glycol monoallyl ether 2000, silicone oil with a hydrogen content of 0.75%, and p-trifluoromethylstyrene as raw materials, and lithium bis(trifluoromethanesulfonylimide) as the lithium salt, the side chains of the siloxane polymer are modified under the catalysis of a Karstedt platinum catalyst. Further utilizing the chemical activity of ethylene oxide at the side chain ends, polyetheramine D400 is used as a crosslinking agent for crosslinking and curing to obtain a solid electrolyte with excellent mechanical properties and good ionic conductivity.
[0032] 3. This invention provides a lithium battery, which is a lithium metal battery assembled with a comb-shaped fluorine-modified polysiloxane solid electrolyte. The specific capacity of the battery can reach 147 mA·g at a charge / discharge rate of 0.5C. -1The theoretical specific capacity of the LiFePO4 cathode is 170 mA·g. -1 After 100 charge-discharge cycles, the battery retains 80% of its capacity. This demonstrates excellent internal chemical stability, with no unnecessary side reactions occurring during cycling. Furthermore, the battery's charge-discharge efficiency consistently remains above 99% throughout the entire cycle. This proves that the insertion and extraction of lithium ions between the positive and negative electrodes is extremely smooth, and the probability of side reactions is very low. Attached Figure Description
[0033] Figure 1 This is a schematic diagram of the comb-shaped fluorine-modified polysiloxane solid electrolyte of the present invention.
[0034] Figure 2 This is a stress-strain curve of the comb-shaped fluorine-modified polysiloxane solid electrolyte of Example 1 of the present invention.
[0035] Figure 3 This is a graph showing the change in battery impedance versus temperature for the Li||SPE||Li button half-cell of Embodiment 2 of the present invention.
[0036] Figure 4 The graph shows the change in battery impedance versus temperature for the Li||SPE||Li button half-cell used in Application Example 2 of this invention.
[0037] Figure 5 The It / impedance curve and calculated ion mobility diagram of the Li||SPE||Li coin symmetric cell used in Example 2 of this invention are shown. Figure 5 The small image in the upper right corner shows the interface impedance R0 before polarization and the interface impedance R after polarization. ss The comparison chart.
[0038] Figure 6 Linear sweep voltammetry curves of the Li||SPE||Li battery in Application Example 2 of the present invention at 30°C and 60°C. Figure 6 (a) is the linear sweep voltammetry curve at 30℃, and (b) is the linear sweep voltammetry curve at 60℃.
[0039] Figure 7 The CV curve is shown for the Li||SPE||LiFePO4 full cell of Application Example 3 of the present invention.
[0040] Figure 8 The graph shows the cycle efficiency of the Li||SPE||LiFePO4 full cell in Application Example 3 of this invention at a capacity of 0.1C.
[0041] Figure 9 The graph shows the cycle efficiency of the Li||SPE||LiFePO4 full cell in Application Example 3 of this invention at 0.5C capacity.
[0042] Figure 10 This is a graph showing the change in battery impedance versus temperature for the Li||SPE||Li button half-cell of Comparative Example 1 of this invention.
[0043] Figure 11 The image shows the It / impedance curve and the calculated ion mobility diagram of the Li||SPE||Li coin symmetric cell of Comparative Example 1 of this invention. Figure 11 The small image in the upper right corner shows the interface impedance R0 before polarization and the interface impedance R after polarization. ss Comparison chart.
[0044] Figure 12 The linear sweep voltammetry curve of the Li||SPE||Li battery of Comparative Example 1 of the present invention at 30°C is shown. Detailed Implementation
[0045] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0046] It should be noted that the technical terms used in this invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments and equipment used in the following embodiments of this invention can be purchased from the market or prepared by existing methods.
[0047] The following specific examples will provide further explanation.
[0048] In this invention, the abbreviation for lithium bis(trifluoromethanesulfonylimide) is LiTFSI.
[0049] Example 1 A comb-shaped fluorine-modified polysiloxane solid electrolyte has the following structure: ; Where m is 44 and n is 23.
[0050] The preparation method of the above-mentioned comb-shaped fluorine-modified polysiloxane solid electrolyte includes the following steps: 10g of APEG2000 and 6g of chloropropylene oxide were added to a reaction vessel and stirred until homogeneous. Sodium hydroxide solid was added in three portions, totaling 1.2g, under ice-water bath conditions. After the solid was completely dissolved, the mixture was transferred to a 50℃ oil bath and reacted for 48 hours. After the reaction was complete, the reaction system was extracted and concentrated to obtain a crude product. A mixed solution of cyclohexane and ethanol (volume ratio 10:1) was added to the crude product, and the mixture was stirred for 30 minutes. The solid was collected, dried, and the product A was obtained. 1.23 g of product A was dissolved in 6 mL of toluene with 133 mg of hydrogen-containing silicone oil and 103.3 mg of p-trifluoromethylstyrene. 4 μL of Karstedt platinum catalyst was added and the mixture was reacted at 70 °C for 10 h to obtain a mixed solution. Then, 300 mg of LiTFSI was added and stirred for 2 h until dissolved. 120 mg of polyetheramine D400 was added to form a mixed solution. The mixed solution was injected into a polytetrafluoroethylene mold and reacted in a vacuum drying oven at 85 °C for 12 h to obtain a comb-shaped fluorine-modified polysiloxane solid electrolyte.
[0051] Mechanical properties of the comb-shaped fluorine-modified polysiloxane solid electrolyte of Example 1 were tested. The specific process was as follows: a strip of polysiloxane solid electrolyte with a length of 40 mm, a width of 10 mm, and a thickness of 0.4 mm was subjected to a tensile test in an electronic universal testing machine at a speed of 5 mm / min to obtain its stress-strain curve.
[0052] Figure 2 This is a stress-strain curve of the comb-shaped fluorine-modified polysiloxane solid electrolyte of Example 1 of the present invention. Figure 2 It can be seen that the maximum elongation at break of the electrolyte is 30%, and the maximum breaking stress is 0.55 MPa.
[0053] Example 2 A comb-shaped fluorine-modified polysiloxane solid electrolyte has the following structure: ; Where m is 22 and n is 23.
[0054] The preparation method of the above-mentioned comb-shaped fluorine-modified polysiloxane solid electrolyte includes the following steps: 10g of APEG1000 and 12g of chloropropylene oxide were added to a reaction vessel and stirred until homogeneous. Then, 2.4g of sodium hydroxide solid was added in three portions over an ice-water bath. After the solid was completely dissolved, the mixture was transferred to an oil bath at 50℃ and reacted for 48 hours. After the reaction was complete, the reaction system was extracted and concentrated to obtain a crude product. A 5:1 (v / v) mixture of cyclohexane and ethanol was added to the crude product, and the mixture was stirred for 30 minutes. The solid was collected, dried, and then the product A was obtained. 1.27 g of product A was dissolved in 8 mL of toluene with 266 mg of hydrogen-containing silicone oil and 206.8 mg of p-trifluoromethylstyrene. 4 μL of Karstedt platinum catalyst was added and the mixture was reacted at 70 °C for 10 h to obtain a mixed solution. Then, 378 mg of LiTFSI was added and stirred for 2 h until dissolved. 160 mg of polyetheramine D400 was added to form a mixed solution. The mixed solution was injected into a polytetrafluoroethylene mold and reacted in a vacuum drying oven at 85 °C for 12 h to obtain a comb-shaped fluorine-modified polysiloxane solid electrolyte.
[0055] The comb-shaped fluorine-modified polysiloxane solid electrolyte prepared in Example 2 was stamped into discs with a diameter of 19 mm. The battery was assembled in the following order: positive electrode shell, steel sheet, comb-shaped fluorine-modified polysiloxane solid electrolyte (SPE), steel sheet, and negative electrode shell. A force of 50 kPa was uniformly applied and compacted on an automated battery packaging machine to obtain a steel sheet|electrolyte|steel sheet battery. The electrochemical performance, i.e., the ionic conductivity, of the electrolyte from Example 2 was tested using a Bio-Logic VSP-3e multichannel electrochemical workstation (France). The ionic conductivity was measured at a frequency range of 1 MHz to 0.1 Hz. The ionic conductivity was calculated using the following formula: σ = l / (R × A). Where σ is the ionic conductivity, l is the thickness of the electrolyte, R represents the intrinsic impedance of the electrolyte, and A is the contact area between the electrolyte and the stainless steel electrode.
[0056] Figure 3 This is a graph showing the change in battery impedance versus temperature for the Li||SPE||Li button half-cell of Example 2 of the present invention. Figure 3 It can be seen from the calculations that the comb-shaped fluorine-modified polysiloxane solid electrolyte can achieve an ionic conductivity of 2.42 × 10⁻⁶ at 60 °C. -4 S·cm -1 .
[0057] Comparative Example 1 A fluorine-free, three-dimensional network-like polysiloxane solid electrolyte, with the following specific structure: .
[0058] The preparation method of the above-mentioned fluorine-free grafted three-dimensional network polysiloxane solid electrolyte includes the following steps: 10g of APEG2000 and 6g of chloropropylene oxide were added to a reaction vessel and stirred until homogeneous. 1.2g of sodium hydroxide solid was added in three portions under ice-water bath conditions. After the solid was completely dissolved, the mixture was transferred to a 50℃ oil bath and reacted for 48 hours. After the reaction was complete, the reaction system was extracted and concentrated to obtain a crude product. The crude product was then placed in a 5:1 volume ratio mixture of cyclohexane and ethanol and stirred. The solid was collected, dried, and then product A was obtained. Product A is APEG2000 with terminal epoxy groups.
[0059] 1.23 g of product A and 66.7 mg of hydrogen-containing silicone oil were dissolved in toluene. 4 μL of Karstedt platinum catalyst was added and the mixture was reacted at 70 °C for 10 h to obtain a mixed solution. 1 mL of acetonitrile was added, followed by 330 mg of lithium bis(trifluoromethanesulfonylimide) and stirring for 2 h until dissolved. 120 mg of polyetheramine D400 was added, and a crosslinking reaction was carried out. The mixed solution was injected into a polytetrafluoroethylene mold and reacted in a vacuum drying oven at 80 °C for 8 h to obtain a fluorine-free, three-dimensional network polysiloxane alkyl solid electrolyte.
[0060] Application Example 1 The comb-shaped fluorine-modified polysiloxane solid electrolyte prepared in Example 1 was stamped to obtain a disc with a diameter of 19 mm. The battery was assembled in the order of positive electrode shell, steel sheet, comb-shaped fluorine-modified polysiloxane solid electrolyte (SPE), steel sheet, and negative electrode shell, and then compacted by uniformly applying a force of 50 kPa on an automated battery packaging machine to obtain a steel sheet|electrolyte|steel sheet battery.
[0061] The electrochemical performance, specifically the ionic conductivity, of the electrolyte corresponding to Example 1 was tested using a Bio-Logic VSP-3e multichannel electrochemical workstation. The frequency range for ionic conductivity was 1 MHz to 0.1 Hz. Ionic conductivity was calculated using the following formula: 。
[0062] in, It is the ionic conductivity. R represents the thickness of the electrolyte, R represents the intrinsic impedance of the electrolyte, and A is the contact area between the electrolyte and the stainless steel electrode.
[0063] Figure 4 This is a graph showing the change in battery impedance versus temperature for the Li||SPE||Li button half-cell used in Application Example 2 of this invention. Figure 4 It can be seen from the calculations that the comb-shaped fluorine-modified polysiloxane solid electrolyte can achieve an ionic conductivity of 2.19 × 10⁻⁶ at 60 °C. -3 S·cm -1 .
[0064] Application Example 2 The comb-shaped fluorine-modified polysiloxane solid electrolyte prepared in Example 1 was stamped into discs with a diameter of 19 mm. The battery was assembled in the following order: positive electrode shell, lithium sheet, comb-shaped fluorine-modified polysiloxane solid electrolyte SPE, lithium sheet, and negative electrode shell. The battery was then compacted by uniformly applying a force of 50 kPa on an automated battery packaging machine to obtain a Li|electrolyte|Li battery.
[0065] The lithium-ion transport number t in Application Example 2 was tested using the AC impedance-chronoamperometry method. Li + The impedance test frequency was 1MHz to 0.1Hz, the polarization voltage was 10mV, and the test time was 3600s to 7200s. The formula for calculating the lithium-ion transport number is as follows: 。
[0066] in, With a polarization voltage of 10mV, For the initial current, For the stabilized current, and These are the interface impedances before and after polarization, respectively.
[0067] Figure 5 The It / impedance curve and calculated ion mobility diagram of the Li||SPE||Li coin symmetric cell used in Example 2 of this invention are shown. Figure 5 The small image in the upper right corner shows the interface impedance R0 before polarization and the interface impedance R after polarization. ss A comparison chart. For example... Figure 5 As shown, calculations reveal that the comb-shaped fluorine-modified polysiloxane solid electrolyte exhibits a lithium-ion transference number of approximately 0.48 at 60°C. This is largely attributed to the flexibility of the polysiloxane segments and the significant effect of the ‒CF3 side chain groups, which allows the Li-ion transference number to increase. + Migration within polymers is even faster.
[0068] The VSP-3e multichannel electrochemical workstation from Bio-Logic, France, was used to test the electrochemical stability window performance of the batteries. The electrochemical stability window was tested at temperatures of 30°C and 60°C, with the ambient temperature precisely controlled using an oven during the testing process. Before each test, the batteries were placed at the test temperature and allowed to stand for 1 hour to reach thermal equilibrium.
[0069] Figure 6 Linear sweep voltammetry curves of the Li||SPE||Li battery in Application Example 2 of the present invention at 30°C and 60°C. Figure 6 In the diagram, (a) shows the linear sweep voltammetry curve at 30℃, and (b) shows the linear sweep voltammetry curve at 60℃. Figure 6As shown in the linear sweep voltammetry (LSV) curves, the upper limits of the electrochemical stability window of the battery at 30℃ and 60℃ are 4.885V and 4.764V, respectively, exhibiting a relatively high electrochemical stability window. This indicates that the inductive effect produced by the incorporation of the ‒CF3 group into the side chain is significant: it reduces the electron cloud density of the Si-O bonds in the polysiloxane backbone and the C / C bonds in the side chain, making oxidation reactions more difficult, thereby increasing the upper limit of the electrolyte's oxidation tolerance and broadening the electrochemical stability window.
[0070] Application Example 3 The comb-shaped fluorine-modified polysiloxane solid electrolyte prepared in Example 1 was stamped into discs with a diameter of 19 mm. The battery was assembled in the following order: positive electrode shell, LiFePO4 positive electrode material, comb-shaped fluorine-modified polysiloxane solid electrolyte (SPE), lithium sheet, and negative electrode shell. A force of 50 kPa was uniformly applied and compacted on an automated battery packaging machine to obtain a LiFePO4|electrolyte|Li battery.
[0071] At 60℃, the electrode potential was controlled to be repeatedly scanned at different rates over time in a triangular waveform, corresponding to the battery in Example 3, once or multiple times. This was used to investigate parameters such as the reversibility of the electrode reaction, the electrode reaction mechanism, and the electrode reaction kinetics. The scanning range was 2.5V to 3.8V.
[0072] Figure 7 This is the CV curve of the Li||SPE||LiFePO4 full cell used in Example 3 of this invention. Figure 7 As shown, there are no other side reactions during the battery charging and discharging process, and it has good reversibility. This indicates that the comb-shaped fluorine-modified polysiloxane solid electrolyte can also have good capacity retention during long-term cycling.
[0073] The constant current charge-discharge performance of the battery corresponding to Case 3 was tested using the Xinwei Battery Testing System. During the test, the ambient temperature was precisely controlled using an oven. To ensure the accuracy of the test results, the battery was placed at a constant temperature for 24 hours before each test to reach thermal equilibrium.
[0074] Figure 8 This is a cycle efficiency graph of the Li||SPE||LiFePO4 full cell in Application Example 3 of this invention at 0.1C capacity. From... Figure 8 It can be seen that the initial discharge specific capacity of the battery at 0.1C is 154 mA·h·g. -1 After 41 cycles, the discharge capacity can still be maintained at 141 mA·h·g. -1 The battery exhibits a capacity retention rate of up to 91% and an average coulombic efficiency of 98.58%. This demonstrates that the battery possesses excellent cycle stability and capacity retention, and it still performs well even when tested at a relatively high rate of 0.5C.
[0075] Figure 9 This is a cycle efficiency graph of the Li||SPE||LiFePO4 full cell in Application Example 3 of the present invention at 0.5C capacity. Figure 9 As shown, the initial discharge specific capacity of the battery at 0.5C is 144 mA·h·g. -1 It also exhibited capacity activation, reaching a capacity of 148 mA·h·g after 8 cycles. -1 After 99 cycles, the discharge capacity can still be maintained at 116 mA·h·g. -1 It has a capacity retention rate of up to 80% and an average coulombic efficiency of 98.95%.
[0076] Figure 10 This is a graph showing the change in battery impedance versus temperature for the Li||SPE||Li button half-cell of Comparative Example 1 of this invention. Figure 10 It can be seen from the calculations that the comparative non-fluorine modified polysiloxane solid electrolyte can achieve an ionic conductivity of 3.11 × 10⁻⁶ at 60 °C. -5 S·cm -1 .
[0077] Figure 11 The image shows the It / impedance curve and the calculated ion mobility diagram of the Li||SPE||Li coin symmetric cell of Comparative Example 1 of this invention. Figure 11 The small image in the upper right corner shows the interface impedance R0 before polarization and the interface impedance R after polarization. ss Comparison chart. (For example) Figure 11 As shown, calculations show that the lithium-ion transference number of the comparative non-fluorine modified polysiloxane solid electrolyte is approximately 0.3 at 60°C.
[0078] Figure 12 This is a linear sweep voltammetry curve of the Li||SPE||Li battery of Comparative Example 1 of the present invention at 30°C. Figure 12 As shown in the linear sweep voltammetry (LSV) curve, the upper limit of the electrochemical stability window of the battery at 30 °C is 4.0 V.
[0079] Therefore, by Figures 10-12 It can be seen that, compared with fluorine modification, Comparative Example 1, due to the lack of fluorine atoms and the lack of synergistic effect, relies solely on the polyether chain to conduct ions, resulting in a decrease in ionic conductivity to 3.11 × 10⁻⁶. -5 S·cm -1 The ion transport number of the polysiloxane solid electrolyte was measured. The electrochemical stability window is only 4.0V.
[0080] In summary, the comb-shaped fluorine-modified polysiloxane solid electrolyte of the present invention exhibits high ionic conductivity and good charge-discharge reversibility, meeting the basic performance requirements of solid electrolytes. When the polymer electrolyte membrane is assembled into a battery, the comb-shaped fluorine-modified polysiloxane solid electrolyte membrane demonstrates good interfacial stability and capacity retention.
[0081] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range, as well as any value between the two endpoints, can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described here to avoid redundancy. Although preferred embodiments of this invention have been described, those skilled in the art, once they understand the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended scope of protection is intended to be interpreted as including the preferred embodiments and all changes and modifications falling within the scope of this invention.
[0082] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of protection of this invention and its equivalents, this invention also intends to include these modifications and variations.
Claims
1. The application of a comb-shaped fluorine-modified polysiloxane solid electrolyte in the preparation of lithium batteries, characterized in that, The polysiloxane solid electrolyte is formed by blending lithium salt and cross-linked comb-shaped fluorine-modified polysiloxane, wherein the cross-linked comb-shaped fluorine-modified polysiloxane has the following structure: ; Where m is 21~44 and n is 6~33; The -CF3 group and comb-like structure are used to simultaneously improve the conductivity and morphological stability of the polysiloxane solid electrolyte - main chain flexibility.
2. The application of the comb-shaped fluorine-modified polysiloxane solid electrolyte according to claim 1 in the preparation of lithium batteries, characterized in that, The cross-linked comb-shaped fluorinated polysiloxane is formed by cross-linking polyetheramine D400 and comb-shaped fluorinated polysiloxane; the molar ratio of lithium salt to oxygen atoms in comb-shaped fluorinated polysiloxane is 1:20, and the lithium salt is lithium bis(trifluoromethanesulfonyl)imide.
3. The application of the comb-shaped fluorine-modified polysiloxane solid electrolyte according to claim 1 in the preparation of lithium batteries, characterized in that, The preparation method of the comb-shaped fluorine-modified polysiloxane solid electrolyte includes the following steps: Using a precursor, hydrogen-containing silicone oil, and p-trifluoromethylstyrene as raw materials, a hydrosilylation reaction is carried out in a solvent and platinum-based catalyst system to obtain a comb-like fluorinated modified polysiloxane; the structure of the precursor is shown below: ; The degree of polymerization m ranges from 21 to 44. Using comb-shaped fluorine-modified polysiloxane and lithium salt as raw materials, the comb-shaped fluorine-modified polysiloxane and the crosslinking agent undergo a crosslinking reaction under the action of a crosslinking agent to obtain a comb-shaped fluorine-modified polysiloxane solid electrolyte.
4. The application of the comb-shaped fluorine-modified polysiloxane solid electrolyte according to claim 3 in the preparation of lithium batteries, characterized in that, The mass ratio of the precursor, hydrogen-containing silicone oil, and p-trifluoromethylstyrene is 1230:133:103.
3.
5. The application of the comb-shaped fluorine-modified polysiloxane solid electrolyte according to claim 3 in the preparation of lithium batteries, characterized in that, The hydrogen-containing silicone oil has a hydrogen mass fraction of 0.75%; the platinum-based catalyst is a Karstedt platinum catalyst.
6. The application of the comb-shaped fluorine-modified polysiloxane solid electrolyte according to claim 3 in the preparation of lithium batteries, characterized in that, The hydrosilylation reaction temperature is 65℃~75℃, and the reaction time is 8h~12h.
7. The application of the comb-shaped fluorine-modified polysiloxane solid electrolyte according to claim 3 in the preparation of lithium batteries, characterized in that, The molar ratio of crosslinking agent to hydrogen-containing silicone oil is 1:
3. The crosslinking agent is polyetheramine with a molecular weight of 400. The crosslinking reaction temperature is 80℃~90℃ and the time is 10h~14h.
8. The application of the comb-shaped fluorine-modified polysiloxane solid electrolyte according to claim 3 in the preparation of lithium batteries, characterized in that, The preparation method of the precursor includes the following steps: using polyethylene glycol monoallyl ether and chloropropylene oxide as raw materials, a substitution reaction is carried out in an ice-water bath under the action of an alkaline catalyst to obtain the precursor.
9. The application of the comb-shaped fluorine-modified polysiloxane solid electrolyte according to claim 8 in the preparation of lithium batteries, characterized in that, The molar ratio of polyethylene glycol monoallyl ether to chloropropylene oxide is 1:6~13; the molecular weight of polyethylene glycol monoallyl ether is 500~2000; the molar ratio of alkaline catalyst to polyethylene glycol monoallyl ether is 6:1, and the alkaline catalyst is sodium hydroxide.
Citation Information
Patent Citations
Fluorine-containing modified polysiloxane solid electrolyte and preparation method and application thereof
CN110571470A
Polysiloxane-based solid electrolyte with ladder-shaped structure and preparation method of polysiloxane-based solid electrolyte
CN121507081A